Approximate Bayesian computation with deep learning supports a third archaic introgression in Asia and Oceania - Mayukh Mondal (Nature Portfolio, 2019)
Introgression of Neanderthals and Denisovans left genomic signals in anatomically modern human after Out-of-Africa event. Here, the authors identify a third archaic introgression common to all Asian and Oceanian human populations by applying an approximate Bayesian computation with a Deep Learning framework.